2022
DOI: 10.1039/d2mh00069e
|View full text |Cite
|
Sign up to set email alerts
|

Photomemristive sensing via charge storage in 2D carbon nitrides

Abstract: We present a photomemristive sensing concept based on light-induced charge storage in the 2D carbon nitride K-PHI. Our design enables memory sensing with tuneable dynamic concentration ranges, combined with diverse operation and readout modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
(106 reference statements)
1
23
0
Order By: Relevance
“…A new absorption band due to photochromism emerged at approximately 670 nm, which is common to all samples. The change in the absorption band of K δ H 3−δ PHI due to photochromism is consistent with that of the solution sample of KPHI. , K δ H 3−δ PHI is classified as a thermally reversible T-type photochromic substance because it shows a reversible color change that gradually returns to yellow at room temperature in all samples . The fact that the same absorption bands appear by photochromism suggests that the excited state in which the sample exhibits a blue color may be approximately independent of δ.…”
Section: Results and Discussionsupporting
confidence: 73%
“…A new absorption band due to photochromism emerged at approximately 670 nm, which is common to all samples. The change in the absorption band of K δ H 3−δ PHI due to photochromism is consistent with that of the solution sample of KPHI. , K δ H 3−δ PHI is classified as a thermally reversible T-type photochromic substance because it shows a reversible color change that gradually returns to yellow at room temperature in all samples . The fact that the same absorption bands appear by photochromism suggests that the excited state in which the sample exhibits a blue color may be approximately independent of δ.…”
Section: Results and Discussionsupporting
confidence: 73%
“…1(b)): Films of K-PHI on indium tin oxide substrates (ITO) were prepared according to a procedure recently described by us. 17,29 In brief, K-PHI was synthesized in a salt melt containing KSCN and the 1D heptazine based polymer melon. 35,44,45 Subsequently, the product was washed, exfoliated via sonication in isopropanol, and homogeneous films of 0.5-2 mm thickness were obtained via dip coating (see Methods section and ESI, † Section S1 for more details).…”
Section: Device Designmentioning
confidence: 99%
“…We recently reported a bifunctional solar battery electrode material based on the fully earth-abundant 2D carbon nitride potassium poly(heptazine imide) (K-PHI). 17 Upon light excitation (bandgap of B2.7 eV), electron-hole pair separation, and extraction of the hole, K-PHI can ''trap'' photoexcited electrons up to several hours 28,29 to days 30,31 and release them on demand, accompanied by a color change from yellow to blue. This combination of optoelectronic and optoionic properties, which are linked to photointercalation of K + ions 32 and electron trapping in an intercalation band within the bandgap produces (pseudo)capacitive electron storage 17,29 and has led to applications in ''dark'' photocatalysis, [33][34][35][36][37] photomemristive sensing, 29 and multifunctional light-driven microswimmers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the absorption band of K-PHI due to photochromism was also consistent with that of the K-PHI solution. 2,5,8,9 The previous study has reported that isolated crystallites of K-PHI tend to aggregate upon freeze-drying. The optical gap of such solid K-PHI was found to increase substantially over the original K-PHI due to a decrease in the conjugation length of the PHI framework and partial detachment.…”
mentioning
confidence: 99%